Kelestarian Sastra Lisan Masyarakat Sai Batin Kabupaten Lampung Barat - Suhardi Suhardi; Yuli Evadianti; Salamah Salamah (LPPM STKIP PGRI Bandar Lampung, 2023)
There are many positive impacts of globalization to support human life today, but it cannot be denied that there is also a negative influence of globalization on regional cultural roots which have actually shaped the character of this nation. Oral literature, as a form of regional culture, has power in terms of human change, through literary works readers/listeners can understand and appreciate various life problems. Efforts are needed to preserve it so that it continues to exist and be sustainable, so that it is able to protect society's morality from the bad influences of globalization. This article attempts to describe the current situation regarding the preservation of the oral literature of the Sai Batin community in West Lampung Regency. This research uses qualitative descriptive methods, data collection uses observation, interview and documentation techniques. Followed by data reduction activities, presentation and drawing conclusions. The research results show that there is oral literature that can be found, including Butettah, Ngehahedo, Nyambai, Muayak as well as Bubandung and Hahiwang. However, some of these things no longer exist in the context of tradition. The existence of Ngehahedo and Muayak is only found on YouTube pages, competitions and art performances.